A matched comparison of the patient-reported outcome measures of cemented and cementless total knee replacements, based on the National Joint Registry of England, Wales, Northern Ireland, and Isle of Man and England’s National PROM collection programme - Mohammad, Hasan R; Judge, Andrew; Murray, David W (Acta Orthopaedica, 2022)
Background and purpose — Total knee replacement (TKR) can be implanted with or without bone cement. It is currently unknown how the functional outcomes compare. Therefore, we compared the patient-reported outcome measures (PROMS) of both fixation methods. Patients and methods — We performed a propensitymatched comparison of 14,404 TKRs (7,202 cemented and 7,202 cementless) enrolled in the National Joint Registry and the English National PROMs collection programme. Subgroup analyses were performed in different age groups (1) < 55 years; (2) 55–64 years; (3) 65–74 years; (4) ≥ 75 years. Results — The 6-month postoperative Oxford Knee Score (OKS) was significantly (p < 0.001) higher for cemented TKR (35, SD 9.7) than cementless TKR (34, SD 9.9). The OKS was also significantly higher for the cemented TKR in all age groups, except the 55–64-year group. A significantly higher proportion of cemented TKRs had an excellent OKS (≥ 41) compared with cementless (32% vs. 28%, p < 0.001) and a lower proportion of poor (< 27) scores (19% vs. 22%, p = 0.001). This was also observed for all age subgroups. There were no significant differences in EQ-5D points gained postoperatively between the groups respectively (0.31 vs. 0.30, p = 0.1). Interpretation — Cemented TKRs had a greater proportion of excellent OKS scores and lower proportion of poor scores both overall and across all age groups. However, the absolute differences are small and below the minimally clinically important difference, making both fixation types acceptable. Currently the vast majority of TKRs are cemented and the results from this study suggest that this is appropriate.